Review on Silk Worm Pupal Meal: A Protein Source in Aquatic Animal Nutrition as a Replacement of Fish Meal - Vishnu, Sunke Suma; Prasad, P. Anand; Lavanya, Ch.; Mamatha, D.; Thriveni, K.; Bhuvaneshwaran, T.; Namdeo, Meshram Supradhnya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Amongst the insect meals, silkworm pupal meal is the most efficient fish meal replacement. It can be utilized in aquatic animal feeds as pupal meal, deoiled silkworm pupal meal and fermented pupal meal, to increase growth performance. It also has a significant impact on animal body composition and digestive enzyme activity. India is the world's second-largest producer of silk, and a vast amount of silkworm pupae waste is discharged into the environment, which can be used as protein in feed. It has a strong nutritional profile that is near or equal to fish meal, consists of 50-80% of crude protein on dry matter, rich in important amino acid profile, (methionine 3.5, lysine 7.0, aspartic acid 10.4, threonine 5.2, serine 5.0, glutamic acid 13.9, proline 5.2, glycine 4.8, alanine 5.8, cystine 1.0, valine 5.5, isoleucine 5.1, leucine 7.5, tyrosine 5.9, phenylalanine 5.1, histidine 2.6, and arginine 5.6) and lipid content ranges from 20-40% in freshly spent pupa and less than 10% in defatted pupa. The oil derived from pupa is high in alpha-linolenic acid, oleic acid, palmitic acid and the gross energy values range from 5.09 to 6.28 MJ/kg. It also contains interesting minerals and vitamins, which piqued the interest of researchers in its use in aqua feed. Aside from the nutritional profile, nutrient digestibility, and the effect of diet on organoleptic quality revealed that SWP meal is equivalent to fish meal in all respects. So, the current review focuses on the effects of silkworm pupal meal on aquatic animals when supplied through diets.